Development of a portable data transfer module for mobile sensing - Mao, XiaoJie (2014)
Today, smart phone plays an important role in our life which allows us not only to communication but also to buy, sell and many other miraculous things. Many modern smart phones add the functionality of portable media players, pocket video cameras and GPS navigation units to form one multi-use device. As the smart phones become more and more convenient and efficient, many people start to develop the mobile application based on the mobile operation system platform to meet the different personal requirements.